7 - Covid-19 Social Relief Programmes and Distribution Mechanisms in East Africa: Lessons Learned - Ivan Kagimu (Africa Development, 2023)
Covid-19 had social, physical and economic impacts that prompted governments to develop strategies to help their citizens cope with the mandatory lockdowns and curfews. East African countries faced several uncertainties and challenges in assisting their citizens, including a lack of funds to implement large-scale relief programmes, effective identification of eligible beneficiaries and viable distribution channels. Some African countries launched cash transfer and social assistance programmes. However, the size, efficiency and proportion of the population covered varied, leading to increased fraud, corruption and embezzlement. Patronage, political exploitation and partisanship were also prevalent. This article aims to assess the success of the East African Covid-19 cash and social assistance programmes and the mechanisms used and to draw lessons by comparing them with effective programmes outside Africa, in order to better inform the efficient design of future similar programmes. Using a data triangulation research methodology, the article finds that the Covid-19 relief programmes in many East African countries failed due to a lack of up-to-date multidimensional data on people's living standards, income and poverty levels. If East African countries are to implement effective social assistance programmes, they need to develop comprehensive and multi-faceted (resident) data collection systems to guide such programmes.